From static to social: Museum-date and the reimagining of urban museums in the disruption era - Farasabila, Tuffana; Sanjatmiko, Prihandoko (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study addresses the shifting public perception of museums in the era of disruption, particularly among urban communities. One manifestation of this shift is the emergence of the museum-date phenomenon, in which museum visits are reimagined as interactive, experiential, and lifestyle-oriented activities. This study aims to investigate how this transformation reflects broader changes in how urban society engages with tourism and cultural institutions. Methods: A qualitative ethnographic method was applied to explore this phenomenon. Data collection involved direct observation, in-depth interviews with key and additional informants, and documentation techniques. Fieldwork was conducted at the National Museum of Indonesia and Lawang Sewu to gather insights into the practices and perceptions surrounding museum-dates in an urban context. Findings: Findings indicate that the disruption era has significantly influenced the dynamics of museum engagement. The concept of the museum-date is not only shaped by disruptive innovations—such as digital culture and social media—but also by a tension with conventional museum frameworks. Visitors are increasingly transforming their museum visits into personalized and performative experiences, reflecting broader changes in urban lifestyles and consumer behavior. The museum-date represents a repackaging of tourism experiences that aligns with the sensibilities of the digital and disruption-driven generation. Conclusion: The study concludes that the museum-date trend signifies a reconfiguration of museum functions in response to disruption-era influences, offering new potential for museums to remain culturally relevant and socially integrated in urban life. Novelty/Originality of this article: This article offers a novel contribution by examining the museum-date as a cultural response to the era of disruption, highlighting how innovation and social media have reshaped urban tourism and museum engagement in Indonesia. It provides a new lens to understand how urban society adapts cultural spaces to meet evolving social needs.